2017
DOI: 10.1088/1361-6455/aa9b8f
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar Bose gas with three-body interactions at finite temperature

Abstract: We investigate effects of three-body contact interactions on a trapped dipolar Bose gas at finite temperature using the Hartree-Fock-Bogoliubov approximation. We analyze numerically the behavior of the transition temperature and the condensed fraction. Effects of the three-body interactions, anomalous pair correlations and temperature on the collective modes are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…The BKT transition and the vortices that accompany it could be analyzed by means of Kibble-Zurek mechanism. One can expect, on the other hand, that the unusual density dependence of the quantum corrections persists also in the presence of three-body correlations [10,37,38]. The insights obtained in the present study may offer a fresh view of the supersolid droplet.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The BKT transition and the vortices that accompany it could be analyzed by means of Kibble-Zurek mechanism. One can expect, on the other hand, that the unusual density dependence of the quantum corrections persists also in the presence of three-body correlations [10,37,38]. The insights obtained in the present study may offer a fresh view of the supersolid droplet.…”
supporting
confidence: 54%
“…Experimentally, the realization of the quantum droplet remains challenging in particular at finite temperatures due to its self-evaporation. One can expect, on the other hand, that the unusual density dependence of the quantum corrections persists also in the presence of the three-body correlations [10,42,43]. Future experimental investigations and Monte Carlo simulation are required in order to fully understand the confidentiality of the droplet state in 2D configuration.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we employ the Hartree-Fock-Bogoliubov (HFB) theory. This scheme has been successfully utilized in 3D dipolar one-component systems with two-and three-body interactions [19][20][21]. Our work reveals two important effects which are dissimilar to a single component BEC, (i) large condensate depletion (ii) near the phase separation and at low temperature, the thermal contribution to the depletion and all thermodynamic quantities has a distinct temperature dependence.…”
Section: Introductionmentioning
confidence: 89%
“…In the context of ultracold atoms with DDI, it has been revealed that the combined effects of TBI and DDI may lead to the formation of a stable supersolid state [28] and a quantum droplet state [29][30][31][32][33]. Very recently, we have shown that the TBI may shift the density profiles, the condensed fraction and the collective modes of a dipolar condensate at finite temperature [34].…”
Section: Introductionmentioning
confidence: 99%